Penerapan Instrumen Evaluasi Kognitif Berbasis HOTS dalam Meningkatkan Kemampuan Berpikir Kritis Peserta Didik pada Materi Fikih - Nurfadhilah Nurfadhilah; Martin Kustati; Nana Sepriyanti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2025)
The implementation of cognitive evaluation of fikih learning seen in the field shows a mismatch between learning objectives and assessment of learning outcomes. Currently, fikih learning is directed to improve students' HOTS-level critical thinking skills in understanding SKI materials. Therefore, this study was conducted with the aim of knowing the concept of HOTS-based cognitive evaluation in fikih materials and the implementation of HOTS-based cognitive evaluation with the improvement of students' thinking skills. This study used a descriptive qualitative approach to explore the implementation of HOTS-based cognitive evaluation in improving students' analytical critical thinking skills. Data collection used observation and interview methods. Data analysis techniques using the Milles and Huberman model include data reduction, data presentation and conclusion drawing. The results showed that the concept of HOTS-based cognitive evaluation in fikih materials includes analysis of learning outcomes, preparation of question grids, making test questions and assessment rubrics, covering cognitive aspects of analyzing, evaluating and creating, so that in its implementation the implementation of HOTS-based cognitive evaluation can improve critical thinking skills and mastery of fikih materials by students well.